In vitro effects of fungicides on conidium germination of Spilocaea oleagina the cause of olive leaf spot - Obanor, E.O.; Walter, M.; Jones, E.E.; Jaspers, M.V. (New Zealand Plant Protection, 2005)
Twenty fungicides were tested in vitro for their effects on the germination of conidia of Spilocaea oleagina the fungus that causes olive leaf spot Conidia used in this evaluation were obtained from naturally infected olive leaves in Canterbury Of the fungicides tested kresoximmethyl and captan were the most effective in preventing conidium germination at low concentrations with EC50 values of 0002 and 0003 g/ml respectively The newer fungicides boscalid and boscalid/pyraclostrobin were also effective (EC500031 and 0006 g/ml respectively) Of the benzimidazole fungicides tested carbendazim was effective (EC500005 g/ml) but thiophanatemethyl was not (EC5026 g/ml) None of the demethylation inhibitor fungicides tested were very effective (EC50 values gt;1 g/ml) except flusilazol (EC500075 g/ml) Two coppercontaining fungicides copper hydroxide and copper sulphate were ineffective for preventing conidium germination (EC5030 and 443 g/ml respectively) This study has identified candidate fungicides for further evaluation as tools for management of olive leaf spot